Issue when expressing a recombinant protein under the control of p35S in Nicotiana tabacum BY-2 cells - Navarre, Catherine; Orval, Rik; Peeters, Marie; Bailly, Nicolas; Chaumont, François (Frontiers in Plant Science, 2023)
Several recombinant proteins have been successfully produced in plants. This usually requires Agrobacterium-mediated cell transformation to deliver the T-DNA into the nucleus of plant cells. However, some genetic instability may threaten the integrity of the expression cassette during its delivery via A. tumefaciens, especially when the protein of interest is toxic to the bacteria. In particular, we found that a Tn3 transposon can be transferred from the pAL4404 Ti plasmid of A. tumefaciens LBA4404 into the expression cassette when using the widely adopted p35S promoter, thereby damaging T-DNA and preventing correct expression of the gene of interest in Nicotiana tabacum BY-2 suspension cells.